Clinical and epidemiological characteristics of imported cases of malaria according to the materials of ZRIDH - Оsadolor, Aisosa Sharon (Запорізький державний медико-фармацевтичний університет, 2025)
Purpose: to study the morbidity of malaria according to the materials of the ZRIDH.
Keywords: тези доповідей